Filter membrane for filtering carbon monoxide at low temperature based on electrostatic spinning and preparation method thereof

CN122895041APending Publication Date: 2026-10-13SHANDONG UNIV OF SCI & TECH +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511837407.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-08
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

虽然静电纺丝本身能高效物理过滤粉尘,但小分子CO的化学惰性使其难以被物理截留,必须依赖催化转化

Benefits of technology

1.本发明采用静电纺丝技术,具有操作简单、工艺可控、对环境友好等特点,制备的纤维滤膜直径可达纳米级,且具有均匀的纤维直径。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a filter membrane for filtering carbon monoxide at low temperature based on electrostatic spinning and a preparation method thereof, and belongs to the technical field of ultrafiltration membrane production.The filter material can realize 95% efficient conversion of CO at 65 DEG C, and the water contact angle of the nanofiber filter membrane can reach 116.6 DEG, so that the filter material has hydrophobic characteristics, can inhibit competitive adsorption of water molecules on active sites in a high-humidity environment, realizes filtering of carbon monoxide at low temperature and high humidity, uniformly loads the catalyst in the three-dimensional network structure through the electrostatic spinning technology, enhances the mass transfer efficiency of CO by using the surface enrichment effect of GO, has a pressure drop of 96.3 Pa at 32 L / min, has excellent hydrophobic performance, humidity resistance and tensile performance, and guarantees the catalytic stability of the downhole working condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ultrafiltration membrane production technology, specifically a filter membrane for low-temperature carbon monoxide filtration prepared by electrospinning and its preparation method. Background Technology

[0002] Carbon monoxide, a major component of incomplete combustion, exhibits significantly elevated concentrations during blasting and mechanical operations, posing a primary toxic gas threat in mining environments. Long-term exposure can lead to acute poisoning and even death, and its colorless and odorless nature contributes to frequent major safety accidents worldwide. In recent years, nanofiber membranes prepared using electrospinning technology have demonstrated unique advantages in particulate matter filtration due to their high porosity and controllable morphology. Their three-dimensional network structure significantly enhances the retention efficiency of micro- and nano-particles through the synergistic effects of multiple mechanisms, including physical interception, electrostatic adsorption, and Brownian diffusion, while maintaining low air resistance due to excellent pore connectivity. Although electrospinning itself can efficiently filter dust physically, the chemical inertness of small-molecule CO makes it difficult to physically retain, necessitating catalytic conversion. The core challenges facing existing technologies are: the development of highly efficient catalysts (especially non-precious metal systems that combine low-temperature activity, moisture resistance, and poisoning resistance) is difficult; catalyst loading can easily lead to changes in fiber structure or embedding of active sites, affecting filtration efficiency or catalytic activity; dust cover can poison the catalyst; the resistance of functionalized filter media prepared by electrospinning increases significantly; the long-term stability and lifespan of catalysts are difficult to guarantee in real complex environments; and large-scale preparation processes are complex and costly. Summary of the Invention

[0003] The purpose of this invention is to provide a filter membrane for low-temperature carbon monoxide filtration based on electrospinning and its preparation method. The filter material of this invention can achieve a CO conversion efficiency of 95% at 65°C, and the water contact angle of the nanofiber filter membrane can reach 116.6°, exhibiting hydrophobic properties. It can achieve low-temperature and high-humidity carbon monoxide filtration by inhibiting the competitive adsorption of water molecules on active sites under high humidity conditions. The catalyst is uniformly loaded into a three-dimensional network structure through electrospinning technology, and the surface enrichment effect of GO is used to enhance the CO mass transfer efficiency. It has a minimum pressure drop of 96.3 Pa at 32 L / min and has excellent hydrophobic, moisture-resistant and tensile properties, providing a new approach for air purification in mines.

[0004] The objective of this invention can be achieved through the following technical solutions: The method for preparing a filter membrane for low-temperature carbon monoxide filtration based on electrospinning includes the following steps: Step 1: Using cerium nitrate hexahydrate and potassium permanganate as raw materials, potassium permanganate is reduced to manganese oxide in an alkaline environment, while releasing active oxygen to promote the oxidation of cerium. Cerium nitrate hexahydrate is hydrolyzed under alkaline conditions to generate cerium hydroxide colloid, which is then directionally grown through hydrothermal reaction and calcined to obtain Mn-modified CeO2-based catalyst. Step 2: Disperse graphene oxide in anhydrous ethanol and sonicate it. Add fluorooctyltriethoxysilane, reflux and stir, then centrifuge to collect the modified graphene oxide. Modify the graphene oxide with a silane coupling agent. Step 3: Prepare coaxial spinning solution. Using PVDF as the spinning matrix, ultrasonically disperse graphene oxide modified with silane coupling agent in N,N-dimethylformamide to obtain an electrospinning shell solution. Using PVDF as the spinning matrix, disperse Mn-CeO2 catalyst in N,N-dimethylformamide to form a uniform catalyst suspension as the core solution. Perform coaxial electrospinning to obtain a filter membrane based on electrospinning that can filter carbon monoxide at low temperatures.

[0005] Preferably, the specific preparation steps of the Mn-modified CeO2-based catalyst are as follows: Cerium nitrate hexahydrate, potassium permanganate, and deionized water were added to a reaction vessel and stirred for 20-30 minutes at 20-25°C and 500-600 rpm to obtain solution A. Then, an 8-9 mol / L sodium hydroxide solution was added to solution A, and stirring was continued for 30-40 minutes. The product was then transferred to a stainless steel reaction vessel lined with polytetrafluoroethylene and stirred for 4-5 hours at 120-130°C and 500-600 rpm. After natural cooling to room temperature, the mixture was filtered, and the filter cake was washed 2-4 times with deionized water and anhydrous ethanol, respectively. The cake was then vacuum dried at 60-70°C for 1-2 hours, ground into powder, and placed in a tube furnace. Under a nitrogen atmosphere, the powder was calcined at 200-230°C for 5-6 hours to obtain the Mn-modified CeO2-based catalyst.

[0006] Preferably, the ratio of cerium nitrate hexahydrate, potassium permanganate, and deionized water is 2.17-2.5g: 7.9-8.2g: 20-30mL.

[0007] Preferably, the ratio of sodium hydroxide solution to solution A is 5.5-6.0 mL: 20-30 mL.

[0008] Preferably, the specific preparation steps for modifying graphene oxide with a silane coupling agent are as follows: 2 mg of graphene oxide was dispersed in 50 mL of anhydrous ethanol and sonicated for 1 h. 0.1 mL of fluoctyltriethoxysilane was added and the mixture was refluxed and stirred at 70°C for 6 h. The modified graphene oxide was collected by centrifugation, washed three times with ethanol, and dried under vacuum at 60°C to obtain silane coupling agent modified graphene oxide.

[0009] Preferably, the specific preparation steps of the electrospinning solution are as follows: Silane coupling agent-modified graphene oxide and N,N-dimethylformamide were added to a reaction vessel and stirred for 20-30 min at 20-25℃ and 500-600 r / min. The mixture was then shaken with an ultrasonic extractor for 30-40 min and stirred for another 4-5 h. Finally, 15-20 wt% PVDF was added and the mixture was stirred for another 8-9 h to obtain an electrospun shell solution. Add 0.5-3.0 wt% Mn-modified CeO2-based catalyst and N,N-dimethylformamide to a reactor and stir for 20-30 min. Then add 15-20 wt% PVDF and continue stirring for 8-9 h to obtain an electrospinning core layer solution.

[0010] Preferably, in the electrospinning shell solution, the ratio of silane coupling agent-modified graphene oxide, N,N-dimethylformamide, and PVDF is 1-2 mg: 5-6 g: 2-3 g. In the electrospinning core layer solution, the ratio of Mn-modified CeO2-based catalyst, N,N-dimethylformamide, and PVDF is 1-2g:5-6g:2-3g.

[0011] Preferably, the specific preparation steps for the filter membrane capable of filtering carbon monoxide at low temperatures based on coaxial electrospinning are as follows: The shell solution is injected into the outer shaft, and the core solution is injected into the inner shaft. A layer of spunbond fabric is placed on the drum to collect electrospun nanofibers, thus obtaining a filter membrane based on electrospinning that can filter carbon monoxide at low temperatures.

[0012] Preferably, the electrospinning voltage is 22-24kV, the shell flow rate is 0.8-1.0mL / h, the core flow rate is 0.2-0.3mL / h, the nozzle-collector distance is 15-20cm, and the operating speed of the drum collector is 100-120r / min.

[0013] The present invention also proposes a filter membrane for low-temperature filtration of carbon monoxide based on electrospinning, which is prepared by the method described above.

[0014] The beneficial effects of this invention are: For the high-temperature and high-humidity environment in mines, a filter membrane that can filter carbon monoxide at a relatively low temperature is prepared using electrospinning technology, which has the following advantages: 1. This invention uses electrospinning technology, which has the advantages of simple operation, controllable process, and environmental friendliness. The prepared fiber filter membrane can reach the nanometer scale in diameter and has a uniform fiber diameter.

[0015] 2. This invention significantly enhances the hydrophobicity of graphene oxide (GO) by modifying it with a silane coupling agent, effectively suppressing the competitive adsorption of water molecules on the active sites of the catalyst under high humidity conditions, and ensuring catalytic stability.

[0016] 2. The nanofiber filter membrane prepared by the invention has a minimum pressure drop of 96.3 Pa at a test flow rate of 32 L / min, and achieves 95% CO conversion efficiency at 65℃, which can provide good personal protection for workers.

[0017] 3. The nanofiber filter membrane prepared by the invention has hydrophobic properties, which can ensure the catalytic stability of downhole operations by inhibiting the competitive adsorption of water molecules on active sites under high humidity conditions.

[0018] 4. The present invention has good tensile properties, and the two-dimensional sheet structure of graphene oxide forms a continuous reinforcing network in the PVDF matrix. Attached Figure Description

[0019] Figure 1 The XRD patterns of Example 3 of the present invention are shown, where (a) is the XRD pattern of the Mn-modified CeO2-based catalyst and (b) is the XRD pattern of nanofiber membranes with different compositions.

[0020] Figure 2 This is a mechanism analysis diagram of the low-temperature carbon monoxide filtering membrane in Examples 1-5 of the present invention.

[0021] Figure 3 The figures shown are a comprehensive analysis of the catalytic performance and characterization of Examples 1-5 of the present invention, where (a) is the CO catalytic performance of the nanofiber membrane and (b) is the H2-TPR curve of the nanofiber membrane.

[0022] Figure 4 The resistance pressure drop test of the fiber membrane after loading GO and catalyst particles in Examples 1-5 is shown in (a) for the filtration pressure drop of the nanofiber membrane at a test flow rate of 32 L / min, and (b) for the air permeability test of the nanofiber membrane.

[0023] Figure 5 The images show the BET test results of the nanofiber membranes in Examples 1-5 of this invention.

[0024] Figure 6 The waterproof performance tests of the nanofiber membranes in Examples 1-5 of the present invention are shown, where (a) is the water contact angle test of the nanofiber membrane and (b) is the hydrostatic pressure performance diagram.

[0025] Figure 7 The tensile properties of the nanofiber membranes in Examples 1-5 of this invention were tested.

[0026] Figure 8This is a schematic diagram showing the adsorption configuration and adsorption energy of CO at different adsorption sites and with different active components after optimization using the DMol3 module in Materials Studio. Detailed Implementation

[0027] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0028] Example 1 The method for preparing a filter membrane for low-temperature carbon monoxide filtration based on electrospinning includes the following steps: S1: 2.17 g of cerium nitrate hexahydrate, 7.9 g of potassium permanganate and 20 mL of deionized water were added to a reaction vessel and stirred for 20 min at 20 °C and 500 r / min to obtain solution A; then 5.5 mL of 8 mol / L sodium hydroxide solution was added to 20 mL of solution A and stirred for another 30 min. The product was then transferred to a stainless steel reaction vessel lined with polytetrafluoroethylene and stirred for 4 h at 120 °C and 500 r / min. After naturally cooling to room temperature, the mixture was filtered, and the filter cake was washed twice with deionized water and anhydrous ethanol, respectively. The cake was then vacuum dried at 60 °C for 1 h, ground into powder, and placed in a tube furnace. Under a nitrogen atmosphere, the powder was calcined at 200 °C for 5 h to obtain the Mn-modified CeO2-based catalyst.

[0029] S2: 2 mg of graphene oxide was dispersed in 50 mL of anhydrous ethanol and sonicated for 1 h. 0.1 mL of fluorooctyltriethoxysilane was added and the mixture was refluxed and stirred at 70°C for 6 h. The modified graphene oxide was collected by centrifugation, washed three times with ethanol, and dried under vacuum at 60°C to obtain silane coupling agent modified graphene oxide.

[0030] S3: Add 1 mg of silane coupling agent-modified graphene oxide and 5 g of N,N-dimethylformamide to a reaction vessel, stir for 20 min at 20 °C and 500 r / min, shake with an ultrasonic extractor for 30 min, continue stirring for 4 h, then add 2 g of 15% PVDF, and continue stirring for 8 h to obtain an electrospinning shell solution; add 1 g of 0.5 wt% Mn-modified CeO2-based catalyst and N,N-dimethylformamide to a reaction vessel, stir for 20 min, then add 2 g of 15 wt% PVDF, and continue stirring for 8 h to obtain an electrospinning core solution.

[0031] S4: The shell solution is injected into the outer shaft and the core solution is injected into the inner shaft. A layer of spunbond fabric is placed on the drum to collect the electrospun nanofibers. Under the conditions of a voltage of 22kV, a shell flow rate of 0.8mL / h, a core flow rate of 0.2mL / h, a nozzle-collector distance of 15cm, and a drum collector operating speed of 100r / min, a layer of spunbond fabric is placed on the drum to collect the electrospun nanofibers, thus obtaining a filter membrane based on electrospinning that can filter carbon monoxide at low temperatures.

[0032] Example 2 The method for preparing a filter membrane for low-temperature carbon monoxide filtration based on electrospinning includes the following steps: S1: 2.3 g of cerium nitrate hexahydrate, 8.1 g of potassium permanganate, and 23 mL of deionized water were added to a reaction vessel and stirred at 22 °C and 530 r / min for 23 min to obtain solution A. Then, 5.7 mL of 8.3 mol / L sodium hydroxide solution was added to 23 mL of solution A and stirred for another 33 min. The product was then transferred to a stainless steel reaction vessel lined with polytetrafluoroethylene and stirred at 123 °C and 530 r / min for 4.3 h. After naturally cooling to room temperature, the mixture was filtered, and the filter cake was washed three times with deionized water and anhydrous ethanol, respectively. The cake was then vacuum dried at 63 °C for 1.3 h, ground, and calcined in a tube furnace at 210 °C for 5.3 h under a nitrogen atmosphere to obtain the Mn-modified CeO2-based catalyst.

[0033] S2: 2 mg of graphene oxide was dispersed in 50 mL of anhydrous ethanol and sonicated for 1 h. 0.1 mL of fluorooctyltriethoxysilane was added and the mixture was refluxed and stirred at 70°C for 6 h. The modified graphene oxide was collected by centrifugation, washed three times with ethanol, and dried under vacuum at 60°C to obtain silane coupling agent modified graphene oxide.

[0034] S3: 1.3 mg of silane coupling agent-modified graphene oxide and 5.3 g of N,N-dimethylformamide were added to a reaction vessel and stirred at 22 °C and 530 r / min for 23 min. The mixture was then shaken with an ultrasonic extractor for 33 min and stirred for another 4 h. 2 g of 16% PVDF was then added and the mixture was stirred for another 8.5 h to obtain an electrospinning shell solution. 1.3 g of 0.8 wt% Mn-modified CeO2-based catalyst and 5.3 g of N,N-dimethylformamide were added to a reaction vessel and stirred for 20 min. 2.3 g of 16 wt% PVDF was then added and the mixture was stirred for another 8 h to obtain an electrospinning core solution.

[0035] S4: The shell solution is injected into the outer shaft and the core solution is injected into the inner shaft. A layer of spunbond fabric is placed on the drum to collect the electrospun nanofibers. Under the conditions of a voltage of 22.5 kV, a shell flow rate of 0.85 mL / h, a core flow rate of 0.22 mL / h, a nozzle-collector distance of 16 cm, and a drum collector operating speed of 105 r / min, a layer of spunbond fabric is placed on the drum to collect the electrospun nanofibers, thus obtaining a filter membrane based on electrospinning that can filter carbon monoxide at low temperatures.

[0036] Example 3 The method for preparing a filter membrane for low-temperature carbon monoxide filtration based on electrospinning includes the following steps: S1: 2.4 g of cerium nitrate hexahydrate, 8.3 g of potassium permanganate, and 25 mL of deionized water were added to a reaction vessel and stirred at 23 °C and 550 r / min for 25 min to obtain solution A. Then, 5.8 mL of 8.5 mol / L sodium hydroxide solution was added to 25 mL of solution A and stirred for another 35 min. The product was then transferred to a stainless steel reaction vessel lined with polytetrafluoroethylene and stirred at 125 °C and 550 r / min for 4.5 h. After naturally cooling to room temperature, the mixture was filtered, and the filter cake was washed three times with deionized water and three times with anhydrous ethanol. The cake was then vacuum dried at 65 °C for 1.5 h, ground, and calcined in a tube furnace at 215 °C for 5.5 h under a nitrogen atmosphere to obtain the Mn-modified CeO2-based catalyst.

[0037] S2: 2 mg of graphene oxide was dispersed in 50 mL of anhydrous ethanol and sonicated for 1 h. 0.1 mL of fluorooctyltriethoxysilane was added and the mixture was refluxed and stirred at 70°C for 6 h. The modified graphene oxide was collected by centrifugation, washed three times with ethanol, and dried under vacuum at 60°C to obtain silane coupling agent modified graphene oxide.

[0038] S3: 1.5 mg of silane coupling agent-modified graphene oxide and 5.5 g of N,N-dimethylformamide were added to a reaction vessel and stirred at 23 °C and 550 r / min for 25 min. The mixture was then shaken with an ultrasonic extractor for 35 min and stirred for another 4.5 h. 2.5 g of 17% PVDF was then added and stirred for another 8.5 h to obtain an electrospinning shell solution. 1.5 g of 1 wt% Mn-modified CeO2-based catalyst and 5.5 g of N,N-dimethylformamide were added to a reaction vessel and stirred for 25 min. 2.5 g of 17 wt% PVDF was then added and stirred for another 8 h to obtain an electrospinning core solution.

[0039] S4: The shell solution is injected into the outer shaft and the core solution is injected into the inner shaft. A layer of spunbond fabric is placed on the drum to collect the electrospun nanofibers. Under the conditions of a voltage of 23kV, a shell flow rate of 0.9mL / h, a core flow rate of 0.24mL / h, a nozzle-collector distance of 17cm, and a drum collector operating speed of 110r / min, a layer of spunbond fabric is placed on the drum to collect the electrospun nanofibers, thus obtaining a filter membrane based on electrospinning that can filter carbon monoxide at low temperatures.

[0040] Example 4 S1: 2.5 g of cerium nitrate hexahydrate, 8.4 g of potassium permanganate, and 27 mL of deionized water were added to a reaction vessel and stirred for 27 min at 24 °C and 570 r / min to obtain solution A. Then, 5.9 mL of 8.7 mol / L sodium hydroxide solution was added to 27 mL of solution A and stirred for another 37 min. The product was then transferred to a stainless steel reaction vessel lined with polytetrafluoroethylene and stirred for 4.7 h at 127 °C and 570 r / min. After naturally cooling to room temperature, the mixture was filtered, and the filter cake was washed three times with deionized water and three times with anhydrous ethanol. The cake was then vacuum dried at 67 °C for 1.7 h, ground, and calcined in a tube furnace at 220 °C for 5.7 h under a nitrogen atmosphere to obtain the Mn-modified CeO2-based catalyst.

[0041] S2: 2 mg of graphene oxide was dispersed in 50 mL of anhydrous ethanol and sonicated for 1 h. 0.1 mL of fluorooctyltriethoxysilane was added and the mixture was refluxed and stirred at 70°C for 6 h. The modified graphene oxide was collected by centrifugation, washed three times with ethanol, and dried under vacuum at 60°C to obtain silane coupling agent modified graphene oxide.

[0042] S3: 1.7 mg of silane coupling agent-modified graphene oxide and 5.7 g of N,N-dimethylformamide were added to a reaction vessel and stirred at 24 °C and 570 r / min for 27 min. The mixture was then shaken with an ultrasonic extractor for 37 min and stirred for another 4.7 h. 2.7 g of 18% PVDF was then added and the mixture was stirred for another 8.7 h to obtain an electrospinning shell solution. 1.7 g of 2 wt% Mn-modified CeO2-based catalyst and 5.7 g of N,N-dimethylformamide were added to a reaction vessel and stirred for 25 min. 2.7 g of 18 wt% PVDF was then added and the mixture was stirred for another 8 h to obtain an electrospinning core solution.

[0043] S4: The shell solution is injected into the outer shaft and the core solution is injected into the inner shaft. A layer of spunbond fabric is placed on the drum to collect the electrospun nanofibers. Under the conditions of a voltage of 23.5 kV, a shell flow rate of 0.95 mL / h, a core flow rate of 0.26 mL / h, a nozzle-collector distance of 18 cm, and a drum collector operating speed of 115 r / min, a layer of spunbond fabric is placed on the drum to collect the electrospun nanofibers, thus obtaining a filter membrane based on electrospinning that can filter carbon monoxide at low temperatures.

[0044] Example 5 S1: 2.5 g of cerium nitrate hexahydrate, 8.2 g of potassium permanganate and 30 mL of deionized water were added to a reaction vessel and stirred for 30 min at 25 °C and 600 r / min to obtain solution A; then 6.0 mL of 9 mol / L sodium hydroxide solution was added to 30 mL of solution A and stirred for another 40 min. The product was then transferred to a stainless steel reaction vessel lined with polytetrafluoroethylene and stirred for 5 h at 130 °C and 600 r / min. After naturally cooling to room temperature, the mixture was filtered, and the filter cake was washed four times with deionized water and anhydrous ethanol, respectively. The cake was then vacuum dried at 70 °C for 2 h, ground into powder, and placed in a tube furnace. Under a nitrogen atmosphere, the powder was calcined at 230 °C for 6 h to obtain the Mn-modified CeO2-based catalyst.

[0045] S2: 2 mg of graphene oxide was dispersed in 50 mL of anhydrous ethanol and sonicated for 1 h. 0.1 mL of fluorooctyltriethoxysilane was added and the mixture was refluxed and stirred at 70°C for 6 h. The modified graphene oxide was collected by centrifugation, washed three times with ethanol, and dried under vacuum at 60°C to obtain silane coupling agent modified graphene oxide.

[0046] S3: 2 mg of silane coupling agent-modified graphene oxide and 6 g of N,N-dimethylformamide were added to a reaction vessel and stirred for 30 min at 25 °C and 600 r / min. The mixture was then shaken with an ultrasonic extractor for 40 min and stirred for another 5 h. 3 g of 20% PVDF was then added and stirred for another 9 h to obtain an electrospinning shell solution. 2 g of 3 wt% Mn-modified CeO2-based catalyst and 6 g of N,N-dimethylformamide were added to a reaction vessel and stirred for 30 min. 3 g of 20 wt% PVDF was then added and stirred for another 8 h to obtain an electrospinning core solution.

[0047] S4: The shell solution is injected into the outer shaft and the core solution is injected into the inner shaft. A layer of spunbond fabric is placed on the drum to collect the electrospun nanofibers. Under the conditions of a voltage of 24kV, a shell flow rate of 1mL / h, a core flow rate of 0.3mL / h, a nozzle-collector distance of 20cm, and a drum collector operating speed of 120r / min, a layer of spunbond fabric is placed on the drum to collect the electrospun nanofibers, thus obtaining a filter membrane based on electrospinning that can filter carbon monoxide at low temperatures.

[0048] like Figure 1 As shown, the crystal structures of different samples were studied by XRD. The diffraction peaks all matched the cubic fluorite structure, and no impurity phase peaks such as MnO, Mn2O3, or Mn3O4 were observed, indicating that Mn entered the CeO2 lattice in the form of dopant and did not form an independent oxide phase. In addition, the intensity ratio of the diffraction peaks of the (311) and (222) crystal planes decreased from 1.2 for pure CeO2 to 0.8 for Mn-CeO2, indicating that Mn doping changed the order of atomic layer stacking, which is consistent with the local structural distortion caused by oxygen vacancies. In contrast, the XRD spectrum of the fabricated fiber membrane ( Figure 1 b) There is no evidence of (222) diffraction peaks, which means that the oxides are effectively distributed in the film, mainly as amorphous crystals, and the addition of fillers does not significantly change the crystal structure of PVDF.

[0049] This invention analyzes the mechanism of a filter membrane prepared by electrospinning that can filter carbon monoxide at low temperatures, and the results are as follows: Figure 2 As shown: GO-PVDF electrospun membranes supported on Mn-CeO2 catalysts efficiently remove CO through a physicochemical synergistic mechanism. The PVDF electrospun fiber network constructs a micro / nano porous framework, providing gas permeation channels and pre-enriching CO. GO sheets adsorb CO molecules via oxygen-containing functional groups and utilize electrostatic potential gradients to directionally transfer them to active sites. The supported Mn-CeO2 catalyst exhibits strong CO adsorption at Mn sites and low oxygen vacancy formation energy. When low-valence ions are doped into the CeO2 matrix, the Ce-O interaction on the material surface weakens, forming CeO2. 3+ -Mn 3+ -Ce 4+ Interactions generate oxygen vacancies. Therefore, the introduction of low-valence impurity elements can effectively improve the defects in the matrix material, thereby enhancing its catalytic oxidation performance. Furthermore, increased defects in the matrix material generate excess electrons that move to the material surface, which is more conducive to the adsorption of oxygen molecules from the surrounding environment by the catalyst, producing adsorbed oxygen anions of different valence states. These adsorbed oxygen anions act as active oxygen on the catalyst surface, participating in the catalytic oxidation of CO. CO is adsorbed on the active sites on the catalyst surface and reacts with the oxygen anions to ultimately generate CO2.

[0050] like Figure 3 As shown, this invention quantitatively detects the CO catalytic filtration efficiency. Observations indicate that materials doped with different concentrations of manganese-cerium oxidant all exhibit strong low-temperature catalytic oxidation capabilities for carbon monoxide gas. 1wt% Mn-CeO2 / GO-PVDF achieves a high conversion efficiency of 95% at 65℃. While the conversion rate further increases to 95.4-96.0% at 65℃ when the loading increases to 2-3wt%, the increase is only slight. H2-TPR results are shown below. Figure 3 As shown in (b), the main reduction peaks of all samples appeared at lower temperatures, ranging from 200°C to 300°C, indicating the presence of more reactive oxygen species in the samples, which is consistent with the results of CO catalytic performance testing.

[0051] like Figure 4 As shown in (a), this invention investigated the effect of GO loading and different concentrations of catalyst particles on the pressure drop of the fiber membrane. The test results showed that after the introduction of GO, the pressure drop of the fiber membrane increased sharply. While GO increases the surface area of ​​the product, it also increases the resistance of the fiber membrane. When the air flow rate was 32 L·min −1 After doping with different concentrations of catalyst particles, the pressure drop of the fiber membrane generally showed a trend of first decreasing and then increasing, with a resistance of 96.3 Pa when the manganese-cerium catalyst doping amount was 1 wt%. Furthermore, with the increase of oxide loading, the permeability of the fiber membrane initially increased and then decreased, consistent with the trend observed in the quality factor analysis. The test results indicate that 1 wt% catalyst doping can optimize the fiber-catalyst interface compatibility, maintaining the permeability of the nanofiber network while suppressing energy dissipation under high-speed flow through surface modification, thus achieving synergistic regulation of low-resistance, high-efficiency filtration.

[0052] BET testing was performed on the fiber membrane to quantitatively characterize its specific surface area and pore size distribution, such as... Figure 5 As shown, specific surface area directly reflects the density of active sites, affecting adsorption capacity, catalytic reaction efficiency, and the intensity of pollutant interfacial interactions, while pore size distribution reveals a hierarchical structure of micropores (<2 nm), mesopores (2–50 nm), and macropores (50 nm). The results indicate that the hierarchical pore structure of the composite material undergoes significant evolution with the introduction of functional components. Pure PVDF fiber membranes exhibit lower specific surface area and smaller average pore size, which is related to the limited porosity formed by their dense fiber stacking. After introducing graphene oxide (GO), the specific surface area increased to 9.6876 m². 2 ·g -1The increase reached 52.1%. Simultaneously, the average pore size expanded to 24.68 nm, indicating that the GO embedding effectively improved pore connectivity. Further loading with 1 wt% Mn-CeO2 catalyst, although the specific surface area did not change significantly, the average pore size further increased to 30.53 nm. The larger pore size reduces fluid resistance, consistent with previous pressure drop test results, while the moderate specific surface area provides an anchoring substrate for active sites, laying the structural foundation for subsequent filtration functionality.

[0053] The high temperature and humidity conditions in underground wells place stringent requirements on the moisture resistance of filter media, necessitating the control of surface wettability to suppress pore blockage and charge attenuation caused by moisture infiltration. Water contact angle testing is as follows... Figure 6 As shown in (a), the contact angle jumps to 116.6° at a 1wt% load, as... Figure 6 As shown in (b), the hydrostatic performance test results are consistent with the contact angle, reaching a maximum value when the oxide loading is 1 wt%. This is attributed to the synergistic effect of the micro-nano composite rough structure induced by the Mn-CeO2 / GO interface and chemical heterogeneity, which effectively locks in the air cushion layer to block water molecule penetration, achieving a balance between moisture resistance and filtration performance, and better coping with the complex downhole environment.

[0054] Tensile testing was conducted to study the mechanical properties of the membrane. Figure 7 Test results demonstrate that the tensile properties of PVDF are significantly improved after the introduction of graphene oxide (GO), mainly due to the continuous reinforcing network formed by the two-dimensional sheet structure of GO within the PVDF matrix. After the introduction of Mn-CeO2 catalyst particles, the tensile properties exhibit a non-monotonic change of "first increasing and then decreasing." Performance gradually increases at low concentrations (0.5wt%-1wt%), as the surface oxygen vacancies of Mn-CeO2 may promote local cross-linking or knotting of PVDF chains, enhancing material rigidity. The optimal performance is achieved at a 1wt% concentration, where Mn-CeO2 reaches its best dispersion state. However, excessive Mn-CeO2 agglomerates due to van der Waals forces or polar interactions, forming micron-sized aggregates that become stress concentration points, ultimately increasing the material's brittleness and decreasing its ductility.

[0055] In addition, this invention also uses the DMol3 module in Materials Studio to perform theoretical simulation optimization of the adsorption configuration and adsorption energy of CO at different adsorption sites and with different active components, specifically as follows: Figure 8As shown in figure a, the adsorption energy of CO at the Mn site in the Mn-doped system is -1.08 eV, which is significantly stronger than its adsorption energy at the Ce site in pure CeO2 (-0.82 eV). This indicates that the Mn atoms introduced by doping provide stronger CO adsorption sites. Notably, the CO adsorption energy at the Ce site after doping (-1.00 eV) is also higher than that at the Ce site in pure CeO2, indicating that Mn doping not only becomes a strong adsorption site itself, but also enhances the adsorption activity of adjacent Ce sites through electronic structure modification. Figure 8 b shows that the energy for oxygen vacancy formation in Mn-doped CeO2 is 2.92 eV, significantly lower than the 3.19 eV of pure CeO2. This indicates that Mn doping greatly promotes the formation of oxygen vacancies on the CeO2 surface / bulk phase. Oxygen vacancies are key active sites for catalytic oxidation reactions in CeO2-based materials, and their easier formation is crucial for enhancing catalytic activity. The electrostatic potential diagram can visually display the differences in charge distribution on the material surface. Figure 8 c reveals the electrostatic potential of Mn-CeO2. After Mn doping, the electrostatic potential around the Mn sites is generally more electron-rich than that of the Ce sites. This corresponds to the stronger adsorption energy of CO at the Mn sites calculated above. The more negative electrostatic potential region is more likely to attract the positively charged carbon ends of CO, enhancing chemisorption. Mn doping effectively modulates the electronic and structural properties of CeO2, introducing highly active Mn-CO adsorption sites and significantly reducing the energy barrier for forming key reaction sites (oxygen vacancies), while simultaneously improving the intrinsic adsorption activity of the Ce sites on the support. These synergistic effects theoretically explain the microscopic mechanism by which Mn-supported catalysts enhance the CO oxidation performance of spun films.

[0056] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention.

Claims

1. A method for preparing a filter membrane capable of filtering carbon monoxide at low temperatures based on electrospinning, characterized in that, Includes the following steps: Step 1: Using cerium nitrate hexahydrate and potassium permanganate as raw materials, potassium permanganate is reduced to manganese oxide in an alkaline environment, while releasing active oxygen to promote the oxidation of cerium. Cerium nitrate hexahydrate is hydrolyzed under alkaline conditions to generate cerium hydroxide colloid, which is then directionally grown through hydrothermal reaction and calcined to obtain Mn-modified CeO2-based catalyst. Step 2: Disperse graphene oxide in anhydrous ethanol and sonicate it. Add fluorooctyltriethoxysilane, reflux and stir, then centrifuge to collect the modified graphene oxide. Modify the graphene oxide with a silane coupling agent. Step 3: Prepare coaxial spinning solution. Using PVDF as the spinning matrix, ultrasonically disperse graphene oxide modified with silane coupling agent in N,N-dimethylformamide to obtain an electrospinning shell solution. Using PVDF as the spinning matrix, disperse Mn-CeO2 catalyst in N,N-dimethylformamide to form a uniform catalyst suspension as the core solution. Perform coaxial electrospinning to obtain a filter membrane based on electrospinning that can filter carbon monoxide at low temperatures.

2. The method for preparing a filter membrane capable of low-temperature carbon monoxide filtration based on electrospinning according to claim 1, characterized in that, The specific preparation steps for the Mn-modified CeO2-based catalyst are as follows: Cerium nitrate hexahydrate, potassium permanganate, and deionized water were added to a reaction vessel and stirred for 20-30 minutes at 20-25°C and 500-600 rpm to obtain solution A. Then, an 8-9 mol / L sodium hydroxide solution was added to solution A, and stirring was continued for 30-40 minutes. The product was then transferred to a stainless steel reaction vessel lined with polytetrafluoroethylene and stirred for 4-5 hours at 120-130°C and 500-600 rpm. After natural cooling to room temperature, the mixture was filtered, and the filter cake was washed 2-4 times with deionized water and anhydrous ethanol, respectively. The cake was then vacuum dried at 60-70°C for 1-2 hours, ground into powder, and placed in a tube furnace. Under a nitrogen atmosphere, the powder was calcined at 200-230°C for 5-6 hours to obtain the Mn-modified CeO2-based catalyst.

3. The method for preparing a filter membrane capable of low-temperature carbon monoxide filtration based on electrospinning according to claim 2, characterized in that, The ratio of cerium nitrate hexahydrate, potassium permanganate, and deionized water is 2.17-2.5g: 7.9-8.2g: 20-30mL.

4. The method for preparing a filter membrane capable of low-temperature carbon monoxide filtration based on electrospinning according to claim 2, characterized in that, The ratio of sodium hydroxide solution to solution A is 5.5-6.0 mL : 20-30 mL.

5. The method for preparing a filter membrane capable of low-temperature carbon monoxide filtration based on electrospinning according to claim 1, characterized in that, The specific preparation steps for modifying graphene oxide with silane coupling agents are as follows: 2 mg of graphene oxide was dispersed in 50 mL of anhydrous ethanol and sonicated for 1 h. 0.1 mL of fluoctyltriethoxysilane was added and the mixture was refluxed and stirred at 70°C for 6 h. The modified graphene oxide was collected by centrifugation, washed three times with ethanol, and dried under vacuum at 60°C to obtain silane coupling agent modified graphene oxide.

6. The method for preparing a filter membrane capable of low-temperature carbon monoxide filtration based on electrospinning according to claim 1, characterized in that, The specific preparation steps of the electrospinning solution are as follows: Graphene oxide and N,N-dimethylformamide were added to a reaction vessel and stirred for 20-30 min at 20-25℃ and 500-600 r / min. The mixture was then shaken with an ultrasonic extractor for 30-40 min and stirred for 4-5 h. Then 15-20 wt% PVDF was added and stirred for 8-9 h to obtain an electrospun shell solution. Add 0.5-3.0 wt% Mn-modified CeO2-based catalyst and N,N-dimethylformamide to a reactor and stir for 20-30 min. Then add 15-20 wt% PVDF and continue stirring for 8-9 h to obtain an electrospinning core layer solution.

7. The method for preparing a filter membrane capable of low-temperature carbon monoxide filtration based on electrospinning according to claim 6, characterized in that, In the electrospinning shell solution, the ratio of graphene oxide, N,N-dimethylformamide, and PVDF is 1-2 mg: 5-6 g: 2-3 g. In the electrospinning core layer solution, the ratio of Mn-modified CeO2-based catalyst, N,N-dimethylformamide, and PVDF is 1-2g:5-6g:2-3g.

8. The method for preparing a filter membrane capable of low-temperature carbon monoxide filtration based on electrospinning according to claim 7, characterized in that, The specific preparation steps of the filter membrane for low-temperature carbon monoxide filtration based on coaxial electrospinning are as follows: The shell solution is injected into the outer shaft, and the core solution is injected into the inner shaft. A layer of spunbond fabric is placed on the drum to collect electrospun nanofibers, thus obtaining a filter membrane based on electrospinning that can filter carbon monoxide at low temperatures.

9. The method for preparing a filter membrane capable of low-temperature carbon monoxide filtration based on electrospinning according to claim 8, characterized in that, The electrospinning voltage is 22-24kV, the shell flow rate is 0.8-1.0mL / h, the core flow rate is 0.2-0.3mL / h, the nozzle-collector distance is 15-20cm, and the working speed of the drum collector is 100-120r / min.

10. A filter membrane for low-temperature carbon monoxide filtration prepared by electrospinning, characterized in that, It is prepared by the preparation method described in any one of claims 1-8.